2016
DOI: 10.1093/jat/bkw125
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Case of Drug-Facilitated Sexual Assault using Chloroform

Abstract: Despite its well-known sedative properties, chloroform is rarely used for drug-facilitated sexual assault (DFSA) as its administration cannot be achieved without the victim's knowledge: we report an unusual case of DFSA using this solvent. A 26-year-old woman declared that her partner get her to sleep using chloroform the previous night. When she waked up at 3 am, her hands were tied. She immediately suspected violence and sexual penetration. Toxicological blood screening using a liquid chromatography-electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…All the included studies are discussed here with regard to the drug being used, but only two (n=2) have reported on the source of the drug [ 13 , 16 ] (Table 2 ).…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…All the included studies are discussed here with regard to the drug being used, but only two (n=2) have reported on the source of the drug [ 13 , 16 ] (Table 2 ).…”
Section: Reviewmentioning
confidence: 99%
“…Three of the included studies mention the use of chloroform for the purpose of DFSA [ 13 , 16 , 17 ]. Richeval et al reported that chloroform is a controlled substance in France and is difficult to obtain.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations